How to stress-test EU policies: Building a more resilient Europe for tomorrow - Fernandes Meenakshi; Heflich Aleksandra; Andersen Tina; Lunkeit Andreas Bjerre; Kaivo-oja Jari; Schmidt-Kessen Maria José (European Parliament, Directorate-General for Parliamentary Research Services, 2022)
Policy-makers are seeking to 'future proof' policies in order to be better prepared for disruptive and unanticipated events. The application of foresight methods such as stress-testing can help achieve this goal. This study introduces a methodology for the European Parliament to stress-test legislation. The method can be integrated into existing law-making and scrutiny processes in the European Parliament. It draws on lessons learnt and recommendations stemming from independent research that encompassed a comprehensive review of reports and research studies, and in-depth research on four countries (Finland, the Netherlands, New Zealand and the United Kingdom), as well as a pilot-test for three policy areas (robotics and artificial intelligence, information and consultation of workers, and competition policy – State aid).